CMOS true‐time delay IC for wideband phased‐array antenna. Issue 6 (11th September 2018) - Kim, Jinhyun; Park, Jeongsoo; Kim, Jeong‐Geun
Abstract : This paper presents a true‐time delay (TTD) using a commercial 0.13‐μm CMOS process for wideband phased‐array antennas without the beam squint. The proposed TTD consists of four wideband distributed gain amplifiers (WDGAs), a 7‐bit TTD circuit, and a 6‐bit digital step attenuator (DSA) circuit. The T‐type attenuator with a low‐pass filter and the WDGAs are implemented for a low insertion loss error between the reference and time‐delay states, and has a flat gain performance. The overall gain and return losses are >7 dB and >10 dB, respectively, at 2 GHz–18 GHz. The maximum time delay of 198 ps with a 1.56‐ps step and the maximum attenuation of 31.5 dB with a 0.5‐dB step are achieved at 2 GHz–18 GHz. The RMS time‐delay and amplitude errors are <3 ps and <1 dB, respectively, at 2 GHz–18 GHz. An output P1 dB of <−0.5 dBm is achieved at 2 GHz–18 GHz. The chip size is 3.3 × 1.6 mm 2, including pads, and the DC power consumption is 370 mW for a 3.3‐V supply voltage. Abstract : Because of their electronic beamforming and low SNR, CMOS‐based phased‐array antennas have been widely applied to radar and communication systems. In this paper, the true‐time delay (TTD), as compared to a phase shifter, provides reduced beam squinting and high resolution through a constant time delay over the applied frequency for wideband phased‐array antennas. In addition, the TTD results in a low insertion loss error and a fl at gain performance with a T‐type attenuator and a distributed amplifi er.